RETURN ON ASSET, DEBT TO ASSET RATIO DAN FAKTOR LAINNYA YANG MEMENGARUHI NILAI PERUSAHAAN - Stephanie, Stephanie; Zubaidi, Umar Issa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to analyze the effect of return on assets, debt to assets ratio, current ratio, firm size, dividend payout ratio, total assets turnover, and assets growth on Firm value. The population used in this study is cyclical and non-cyclical consumer companies listed on the Indonesia Stock Exchange during 2020 to 2022. Sampling is done with the purposive sampling method and the analysis method used is the multiple regression method. There are 34 companies from consumer cyclical and non-cyclical companies that meet the sampling criteria and are taken as a sample in this study. The results of this study show that statistically the return on assets and debt to assets ratio have a positive effect on firm value. Current ratio, firm size, dividend payout ratio, total assets turnover, and assets growth do not affect on firm value.Firm